Fatores da satisfação do cidadão com a gestão pública: um estudo sobre o orçamento participativo municipal - França, Adamires (2008)
This thesis deals with the quality dimensions and factors affecting citizens satisfaction in the participatory budgeting process in a major city of Brazil. Participatory budgeting was introduced as a usual practice in many Brazilian cities since the 1990s. It is adapted a model proposed by Johnson et al. (2001) of customer satisfaction and loyalty antecedent factors with constructs related to governance also included, to evaluate the quality perception and satisfaction rates by citizens representatives in the participatory budgeting process. It is conducted a survey with a sample of 84 citizens representatives of the seven city regions of Natal, the capital of a Northeastern State of Brazil. It is applied descriptive and multiple regression statistical analysis. The main findings related to quality and governance constructs are that the quality factors are the main factors affecting satisfaction but also the tax construct is significative to satisfaction. More regarding it was found that for different perspective of the satisfaction there are different set of factors affecting it